In silico investigation of cholesterol-lowering drugs to find potential inhibitors of dehydrosqualene synthase in Staphylococcus aureus - Bhogal, Inderjeet; Pankaj, Vaishali; Provaznik, Valentine; Roy, Sudeep (3 Biotech, 2024)
UNLABELLED: Staphylococcus aureus is a lethal pathogen that can cause various bacterial infections. This study targets the CrtM enzyme of S. aureus, which is crucial for synthesizing golden carotenoid pigment: staphyloxanthin, which provides anti-oxidant activity to this bacterium for combating antimicrobial resistance inside the host cell. The present investigation quests for human SQS inhibitors against the CrtM enzyme by employing structure-based drug design approaches including induced fit docking (IFD), molecular dynamic (MD) simulations, and binding free energy calculations. Depending upon the docking scores, two compounds, lapaquistat acetate and squalestatin analog 20, were identified as the lead molecules exhibit higher affinity toward the CrtM enzyme. These docked complexes were further subjected to 100 ns MD simulation and several thermodynamics parameters were analyzed. Further, the binding free energies (ΔG) were calculated for each simulated protein-ligand complex to study the stability of molecular contacts using the MM-GBSA approach. Pre-ADMET analysis was conducted for systematic evaluation of physicochemical and medicinal chemistry properties of these compounds. The above study suggested that lapaquistat acetate and squalestatin analog 20 can be selected as potential lead candidates with promising binding affinity for the S. aureus CrtM enzyme. This study might provide insights into the discovery of potential drug candidates for S. aureus with a high therapeutic index. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13205-023-03862-y.